Defence spending and military modernisation : should it be recession-proof? - Bitzinger, Richard A. (2009)
Given the current global economic crisis, there is growing debate over whether defence budgets should be recession-proof. National security is a first-order priority for any country. Yet, militaries should never be given a blank check when it comes to spending. The decision to shield dfence budgets during tough econnomic times is ultimately a political one.